2004
DOI: 10.1101/gad.291504
|View full text |Cite
|
Sign up to set email alerts
|

Pax5 inducesV-to-DJrearrangements and locus contraction of theimmunoglobulin heavy-chaingene

Abstract: Cold Spring Harbor Laboratory Press on May 11, 2018 -Published by genesdev.cshlp.org Downloaded from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
457
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(488 citation statements)
references
References 59 publications
20
457
4
1
Order By: Relevance
“…Long-range recombination of V gene segments at all Ig and Tcr loci is facilitated by a contraction process, which places the V cluster into spatial proximity with distal (D)J targets located 0.1-3.2 Mb away in the linear genome (3,25). Deletion of transcription factors or cis elements that disrupt locus contraction significantly impair V to (D)J recombination, supporting a functional link between these processes (13,(26)(27)(28). Additional evidence indicates that V clusters fold into a compact rosettelike structure, which may permit extensive interactions between a recombination center and many or all of its upstream V segments (14).…”
Section: Spatial Access Of Vβ Gene Segments To the Dβjβ Recombinationmentioning
confidence: 99%
“…Long-range recombination of V gene segments at all Ig and Tcr loci is facilitated by a contraction process, which places the V cluster into spatial proximity with distal (D)J targets located 0.1-3.2 Mb away in the linear genome (3,25). Deletion of transcription factors or cis elements that disrupt locus contraction significantly impair V to (D)J recombination, supporting a functional link between these processes (13,(26)(27)(28). Additional evidence indicates that V clusters fold into a compact rosettelike structure, which may permit extensive interactions between a recombination center and many or all of its upstream V segments (14).…”
Section: Spatial Access Of Vβ Gene Segments To the Dβjβ Recombinationmentioning
confidence: 99%
“…In pro-B nuclei, the IgH locus is centrally located and undergoes large-scale compaction. This compacted state facilitates long-range V-to-DJ rearrangements, particularly of the distal V H J558 genes (Kosak et al, 2002), and it is mediated by the transcription factor Pax5 (Fuxa et al, 2004). In thymocytes, however, the inactive IgH locus is mainly localized at the nuclear periphery through an interaction with the nuclear lamina or its associated proteins, but not with centromeric heterochromatin (Kosak et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…DJ H -distal V H gene segments are blocked from undergoing V H -to-DJ H rearrangement in pro-B cells from Pax5-deficient mice (Urbanek et al, 1994;Nutt et al, 1997;Hesslein et al, 2003). Until recently, there was evidence for two roles of Pax5 in controlling V H -to-DJ H rearrangements: (a) facilitating rearrangement of distal V H genes by inducing IgH locus contraction (Fuxa et al, 2004), and (b) removing histone H3 methylated at lysine 9, a marker of repressed chromatin, from the V H locus, making V H genes accessible for V H -to DJ H recombination (Johnson et al, 2004). In addition, we recently reported that Pax5 binds to V H coding regions and to the RAG1/ RAG2 complex, which may facilitate RAG mediated recombination of individual V H genes (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been slow, but a recent report that certain mouse V H clusters have PAX5 target elements harboring intrinsic enhancer activity may provide a much-needed boost (27). Beyond chromatin accessibility, it is now clear that the three-dimensional structure of AgR loci plays an important role in facilitating long-range recombination, including V to DJ H (28,29). However, the cause-effect relationships, if any, among chromatin accessibility, transcription, and changes in locus topology remain key questions for the future.…”
Section: Preparing Targets For V(d)j Recombinase: Transcription Pavesmentioning
confidence: 99%